2012
DOI: 10.1097/inf.0b013e31825691e4
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Complete Blood Cell Count in Late-onset Neonatal Sepsis

Abstract: Background Late-onset sepsis is an important cause of morbidity and mortality in infants. Diagnosis of late-onset sepsis can be challenging. The complete blood cell count and differential have been previously evaluated as diagnostic tools for late-onset sepsis in small, single-center reports. Objective We evaluated the diagnostic accuracy of the complete blood count and differential in late-onset sepsis in a large multicenter population. Study design Using a cohort of all infants with cultures and complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 24 publications
4
70
0
1
Order By: Relevance
“…Differential WBC presence would be expected to modify the type of RNA recovered, but we did not identify statistically significant alterations in circulating WBCs between groups. This finding further substantiates the documented limitations of WBC and WBC indices to identify infected preterm infants (40,41). Minimal mortality in our cohort prevented meaningful comparisons between survivors and nonsurvivors.…”
Section: Discussionsupporting
confidence: 64%
“…Differential WBC presence would be expected to modify the type of RNA recovered, but we did not identify statistically significant alterations in circulating WBCs between groups. This finding further substantiates the documented limitations of WBC and WBC indices to identify infected preterm infants (40,41). Minimal mortality in our cohort prevented meaningful comparisons between survivors and nonsurvivors.…”
Section: Discussionsupporting
confidence: 64%
“…43 High and low WBC, high Absolute Neutrophil count (ANC), high I/T ratios, and low platelet counts were associated with LOS. 44 However, a single blood cell count-derived index did not have proven sensitivity to reliably exclude EOS or LOS in neonates. 43,44 The absolute immature neutrophil count and absolute neutrophil count have suboptimal sensitivity and decreased predictive accuracy for EOS as elevation does not consistently distinguish an inflammatory response from a noninfectious etiology.…”
Section: Neutrophil Number and Functionmentioning
confidence: 99%
“…44 However, a single blood cell count-derived index did not have proven sensitivity to reliably exclude EOS or LOS in neonates. 43,44 The absolute immature neutrophil count and absolute neutrophil count have suboptimal sensitivity and decreased predictive accuracy for EOS as elevation does not consistently distinguish an inflammatory response from a noninfectious etiology. 45 The I/T ratio is a more sensitive indicator of sepsis; however, single assessments have a better negative predictive value (99%) than positive predictive value (25%).…”
Section: Neutrophil Number and Functionmentioning
confidence: 99%
“…Apart from that, neutropenia which is very common and more sensitive in diagnosis of sepsis has a similar score as leukocytosis which is frequently seen in neonates due to non-specific reasons. 13,14 Recent recognition of role of nucleated RBCs in neonatal sepsis deserves its inclusion in diagnosis of sepsis. The modified HSS designed by us have incorporated the above facts.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have highlighted the diagnostic ability of neutropenia to be higher than leukocytosis in neonatal sepsis. 13,14 Study observed that neutropenia was strongly associated with sepsis and hence deserved a higher weightage. Hence, we increased the weightage to two (instead of one in HSS) of this parameter to obtain the modified HSS (Table 1).…”
Section: Introductionmentioning
confidence: 99%